Hermite–Hadamard-type inequalities for multiplicative harmonic s-convex functions - Özcan, Serap; Uruṣ, Ayça; Butt, Saad Ihsan (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We study the concept of multiplicative harmonic s-convex functions and establish Hermite–Hadamard integral inequalities for this class of functions. Furthermore, we derive a set of Hermite–Hadamard-type inequalities applicable to the product and quotient of multiplicative harmonic s-convex functions. In addition, we deduce new inequalities involving multiplicative integrals for the product and quotient of harmonic convex and multiplicative harmonic s-convex functions. Some results for the class of multiplicative harmonic convex functions are obtained as special cases of our results. The obtained results are verified by providing examples with included graphs.